Randomized clinical trial of bedtime sublingual cyclobenzaprine (TNX-102 SL) in military-related PTSD and the role of sleep quality in treatment response. (July 2021) - Sullivan, Gregory M.; Gendreau, R. Michael; Gendreau, Judith; Peters, Perry; Peters, Ashild; Engels, Jean; Daugherty, Bruce L.; Vaughn, Benjamin; Weathers, Frank W.; Lederman, Seth
Highlights: I Military-related PTSD responds poorly to current pharmacotherapies Sublingual cyclobenzaprine 5.6 mg for 12 weeks nominally reduced PTSD severity over placebo Improvement in sleep and psychosocial function also observed Early sleep improvement predicted degree of improvement in PTSD severity Treatment was well tolerated with numerically higher completion rates in drug over placebo Abstract: Effective posttraumatic stress disorder (PTSD) pharmacotherapy is needed. This 12-week randomized multicenter trial evaluated efficacy and safety of TNX-102 SL, a bedtime sublingual formulation of cyclobenzaprine, in patients with military-related PTSD randomized to TNX-102 SL 2.8 mg or 5.6 mg, or placebo. Primary analysis comparing change from baseline in Clinician-Administered PTSD Scale-5 score between 2.8 mg (n=90) and placebo (n=92) was not significant. Secondary analysis of 5.6 mg (n=49) vs placebo demonstrated a mean difference of -4.5 units, p=.05, or, accounting for missing data by multiple imputation, -5.0 units, p=.03. Clinician Global Impression – Improvement responder rate was greater in 5.6 mg than placebo (p=0.04), as was mean functional improvement in Sheehan Disability Scale social domain (p=.03) and trended in work domain (p=.05). Post-hoc analyses showed early sleep improvement predicted improvement in PTSD after 12 weeks for TNX-102 SL (p<.01), not for placebo. Most common administration site reaction in TNX-102 SL groups was oral hypoaesthesia (5.6 mg, 36%; 2.8 mg, 39%; placebo, 2%), while most common systemic adverse event was somnolence (5.6 mg, 16%; 2.8 mg, 12%; placebo, 6%). This provides preliminary evidence that TNX-102 SL 5.6 mg reduces PTSD symptoms, improves sleep and psychosocial function, and is well tolerated. Clinicaltrials.gov Identifier: NCT02277704